A good dog : the story of Orson, who changed my life - Katz, Jon. (New York : Random House Trade Paperback, 2007)
"People who love dogs often talk about a 'lifetime' dog. I'd heard the phrase a dozen times before I came to recognize its significance. Lifetime dogs are dogs we love in especially powerful, sometimes inexplicable ways." Author Katz tells the story of his lifetime dog, Orson: a beautiful border collie--intense, smart, crazy, and unforgettable. From the moment Katz and Orson meet, their relationship is deep, stormy, and loving. Two years old, Katz's new companion is a great herder of school buses, a scholar of refrigerators, but a dud at herding sheep. Everything Katz attempts--obedience training, herding instruction, a new name, herb and alternative therapies-- helps a little but not enough, and not for long. While Katz is trying to help his dog, Orson is helping him, shepherding him toward a new life on a two-hundred-year- old hillside farm in upstate New York.--From publisher description.
Keywords: Katz, Jon; Dogs -- New Jersey -- Anecdotes; Dogs -- Behavior -- New Jersey -- Anecdotes; Human-animal relationships -- New Jersey -- Anecdotes; Border collie -- New Jersey -- Anecdotes